Host specificity and age-dependent resistance to Cryptosporidium avium infection in chickens, ducks and pheasants - Holubová, Nikola; Sak, Bohumil; Hlásková, Lenka; Květoňová, Dana; Hanzal, Vladimír; Rajský, Dušan; Rost, Michael; McEvoy, John; Kváč, Martin (Experimental parasitology, 2018)
Host- and age-specificity of Cryptosporidium avium were studied in 1-, 21- and 365-day-old chickens (Gallus gallus), domestic ducks (Anas platyrhynchos) and ring-necked pheasants (Phasianus colchicus) under experimental conditions. Cryptosporidium avium was not infectious for ring-necked pheasants, but it was infectious for ducks and chickens at all age categories. The course of infection in ducks did not differ among age categories, but 365-day-old chickens had less severe infections than 1- and 21-day-old chickens. The patent period in chickens and ducks was >30 DPI, but ducks started to shed oocysts of C. avium earlier (5-6 DPI) and at a lower intensity (accumulated value of infection intensity of 58,000-65,000 OPG) than chickens (9-11 DPI and accumulated value of infection intensity of 100,000-105,000 OPG). Experimentally infected birds showed no clinical signs of cryptosporidiosis.
Keywords: kur domácí; Animals; kachny; RNA ribozomální; feces; Feces; Age Factors; polymerázová řetězová reakce; Chickens; Cryptosporidium avium; Polymerase Chain Reaction; Ducks; Poultry Diseases; oocysty; odolnost vůči nemocem; Disease Resistance; věkové faktory; divoká zvířata; Cryptosporidiosis; Oocysts; nemoci ptáků; gastrointestinální obsah; nemoci drůbeže; Transmission study; Cryptosporidium; Host Specificity; Gastrointestinal Contents; Bird Diseases; RNA, Ribosomal; Galliformes; DNA, Protozoan; Animals, Domestic; Animals, Wild; protozoální DNA; Czech Republic; Course of infection; Genotyping Techniques; genotypizační techniky; Česká republika; kryptosporidióza; hospodářská zvířata; zvířata; Anseriformes; hostitelská specificita